1994
DOI: 10.1111/j.1750-3639.1994.tb00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nuclear DNA Fragmentation Following Hypoxia‐Ischemia in the Infant Rat Brain, and Transient Forebrain Ischemia in the Adult Gerbil

Abstract: Wistar rats, eight days old, were subjected to permanent bilateral forebrain ischemia, followed by hypoxia for 15 minutes. A cerebral infarct, mainly involving the cerebral neocortex, hippocampus, amygdala, striatum and subcortical white matter was produced. Neurons and glia showing punctate chromatin condensation and karyorrhectic cells were observed 12 hours after hypoxia-ischemia. Their number increased during the first two days and recruitment of cells with degenerating nuclei occurred until day five. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
59
0
5

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(67 citation statements)
references
References 45 publications
3
59
0
5
Order By: Relevance
“…The injury resulting is similar to that seen in the term human infant that has been exposed to an H-I insult. We have found recently that BDNF markedly protects against the H-I injury in this model, a portion of which has features of apoptotic-like death (Ferrer et al, 1994;Mehmet et al, 1994;Hill et al, 1995;Sidhu et al, 1997;Silverstein et al, 1997;Hasegawa et al, 1998;Pulera et al, 1998) and is caspase dependent (Cheng et al, 1998;Han et al, 2000). Our results in the present study supporting the involvement of the ERK pathway in this protection may have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…The injury resulting is similar to that seen in the term human infant that has been exposed to an H-I insult. We have found recently that BDNF markedly protects against the H-I injury in this model, a portion of which has features of apoptotic-like death (Ferrer et al, 1994;Mehmet et al, 1994;Hill et al, 1995;Sidhu et al, 1997;Silverstein et al, 1997;Hasegawa et al, 1998;Pulera et al, 1998) and is caspase dependent (Cheng et al, 1998;Han et al, 2000). Our results in the present study supporting the involvement of the ERK pathway in this protection may have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons are thus thought to be fragile and very sensitive to such stress, and, as a consequence, apoptotic cell death occurs (2,3). Several studies have shown that caspases are involved in this neuronal apoptosis triggered by brain ischemia.…”
mentioning
confidence: 99%
“…Because it is considered that this period provides a therapeutic window after ischemic injury, there have been attempts to elucidate the exact mechanism of ischemia-induced neuronal cell death. Recently, evidence emerged that neurons are very fragile and sensitive to ischemic stress compared to glial cells and consequently undergo apoptotic cell death (Ferrer et al, 1994;Nitatori et al, 1995). The molecular mechanisms that trigger delayed neuronal cell death are not fully understood; however, hypotheses include the excitotoxicity of glutamate, a disturbed calcium homeostasis, an altered lipid metabolism, free radicals, and mitochondrial involvement (Abe et al, 1995;Juurlink and Sweeney, 1997).…”
mentioning
confidence: 99%